2022
DOI: 10.3390/biomedicines10051081
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute Kidney Disease Severity in Hospitalized Patients with Acute Kidney Injury

Abstract: Acute kidney disease (AKD) forms part of the continuum of acute kidney injury (AKI) and worsens clinical outcomes. Currently, the predictors of AKD severity have yet to be established. We conducted a retrospective investigation involving 310 hospitalized patients with AKI and stratified them based on the AKD stages defined by the Acute Dialysis Quality Initiative criteria. Demographic, clinical, hematologic, and biochemical profiles, as well as 30-day outcomes, were compared between subgroups. In the analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Adult studies have shown even more variability with incidence ranging from 3.8% in the general adult population of a single Canadian territory to 4.4%-74% in adults of special populations including those undergoing cardiac and non-cardiac procedure, chemotherapy, hematopoietic stem cell transplant recipients, those with AKI, heart failure, sepsis, cirrhosis, and SARS-CoV-2 infection (20). Hospitalized adults with AKI admitted to both the general floors as well as ICUs had high prevalence of AKD with most studies showing about one-fourth to half of all patients developing AKD (19,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Adults with cardiac diseases, post cardiac surgery, sepsis and cirrhosis all had high AKD prevalence suggesting hemodynamic status may play a significant role in sustained kidney injury and progression (17,18,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)48).…”
Section: Epidemiology Of Akdmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult studies have shown even more variability with incidence ranging from 3.8% in the general adult population of a single Canadian territory to 4.4%-74% in adults of special populations including those undergoing cardiac and non-cardiac procedure, chemotherapy, hematopoietic stem cell transplant recipients, those with AKI, heart failure, sepsis, cirrhosis, and SARS-CoV-2 infection (20). Hospitalized adults with AKI admitted to both the general floors as well as ICUs had high prevalence of AKD with most studies showing about one-fourth to half of all patients developing AKD (19,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Adults with cardiac diseases, post cardiac surgery, sepsis and cirrhosis all had high AKD prevalence suggesting hemodynamic status may play a significant role in sustained kidney injury and progression (17,18,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)48).…”
Section: Epidemiology Of Akdmentioning
confidence: 99%
“…There have been more comprehensive studies of risk factors for AKD development in adults as outlined in Table 4. In hospitalized adults with AKI, age, gender, intrinsic kidney disease, AKI stage, oliguria, anuria, nephrotoxin exposure, early need for dialysis, BUN level, diabetes, anemia, and respiratory failure have been associated with AKD development (31)(32)(33). In adults admitted to an ICU setting age, male sex, African American race, sepsis, lower baseline eGFR and CKD, anemia, and lower ejection fraction have been shown to be risk factors for AKD (35,39,45).…”
Section: Epidemiology Of Akdmentioning
confidence: 99%
“…Patients suffering from COVID-19 show various degrees of kidney damage caused by the virus. This can be evaluated based on blood urea nitrogen (BUN), creatinine levels, and other structural changes including edema or inflammation of renal parenchyma, focal fibrosis, epithelial cell necrosis with interstitial hyperemia [37,38]. Increased release of proinflammatory factors in response to the viral attack is associated with the development of COVID-19-related acute kidney injury [39].…”
Section: Demographic Details Of the Participantsmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a prevalent condition among the elderly, often leading to detrimental outcomes such as decreased autonomy, increased hospitalization rates, and higher mortality (1). This disease is commonly associated with chronic conditions that contribute to fraility, including hypertension, coronary artery disease, arterial fibrillation, congestive heart failure, stroke, and peripheral vascular disease (2,3). Furthermore, CKD has been identified as a predictor of disability in older adults.…”
Section: Introductionmentioning
confidence: 99%